PS 14-35 INFLUENCE OF AZILSARTAN MEDOXOMIL ON CENTRAL AORTIC BLOOD PRESSURE AND AMBULATORY BLOOD PRESSURE IN PATIENTS WITH MILD TO MODERATE ESSENTIAL HYPERTENSION. (September 2016) - Dobrokhod, Anna; Sirenko, Yuriy; Zhivilo, Irina; Torbas, Olena; Granich, Vladimir; Radchenko, Anna; Primac, Galina; Sydorenko, Piotr; Polishchuk, Sergey; Kushnir, Svetlana
Abstract : Objective: This study was planned to assess influence of azilsartan medoxomil (AZL) on central aortic blood pressure (CAP) and 24-hours blood pressure (BP) in patients with mild to moderate hypertension. Design and Method: Twenty-nine patients (75% men, all white, mean age – 43 years) with mild to moderate essential hypertension, never treated before, were enrolled. Dose of AZL was gradually increased until maximum 80 mg once-daily. Follow-up of the study amounted to 6 months. CAP measurement (SphygmoCor CVMS, Atcor, Australia) and 24-hours blood pressure monitoring (ABPM, Meditech, Hungary) were measured before treatment and on the last visit. Results: Mean value (mean ± SEM) of baseline 24-hours systolic BP (SBP) was 144 ± 1.8 mmHg and 24-hours diastolic BP (DBP)–85 ± 1.6 mmHg, while mean value of CAP was 139 ± 2.9 mmHg. At the end of the study mean value of 24-hours SBP was 128 ± 1.9 mmHg, 24-hours DBP–77 ± 2.1 mmHg and CAP was 121 ± 3, 0 mmHg. So decrease from baseline to final CAP, 24-hours SBP and 24-hours DBP were −18, −16 and −8 mmHg respectively. An outcome of the study shows a significant reduction in both 24-hours SBP and DBP (p < 0.0001) and CAP changes (p < 0.005). Conclusions: Once-daily AZL effectively lowers CAP in adults with mild to moderate essential hypertension and has shown good antihypertensive efficacy according to 24-hours blood pressure monitoring as well.